“Let’s Get on the Same Page”: Clarifying Language Policy Discussions - Elise, S (Eurasian Journal of Philology Science and Education, 2015)
Language is most generally, a systematic way of communication. Language can be linguistic (verbal communication), extra-linguistic (“body language” or sign language), but regardless, both implicitly and explicitly, language is and must be systematic in order to be istinguished from the articulation of random morphemes and/or gesticulations. Beyond its mechanics, language has also been an instrumental tool in implementing ideological agendas, and transforming large swaths of people and communities. The development of nation-states that transcended or cut-across historic ethno-linguistic communities “necessitated” the need for languages of wider communication which would transcend local and regional particularities. As Robert Cooper (1989) writes “Language, of course, can not only be fashioned into a supreme symbol of the common destiny, it can be manipulated to help create the perception of a common destiny” [6]. In light of increasingly complicated geo-political governance systems, this paper looks at Sjaak Kroon’s use of a cube to illustrate how language policy discussions canbe organized in linguistics and language education classrooms and research.Язык вообще наиболее систематический способ коммуникации. Язык может быть лингвистическим (вербальная коммуникация), экстралингвистическим ("язык тела" или язык жестов), но независимо ни от чего язык должен быть систематичным, чтобы исключить артикуляцию случайных морфем и/или жестов. Вне его механики язык является инструментом в осуществлении идеологических программ и преобразований больших рядов людей и сообществ. Развитие этнических государств, которые приумножились или сократились через исторические ethno-лингвистические сообщества, вызывало необходимость в языках более широкой коммуникации, которая превысит местные и региональные особенности. Роберт Купер (1989) пишет, что “язык, конечно, может не только быть вылеплен в высший символ общей судьбы, им можноуправлять, чтобы помочь создать восприятие общей судьбы” [6]. В свете все более и более сложных geo-политических систем управления обсуждение языковой политики может быть организовано в языковых образовательных классных комнатах и в лингвистических исследованиях.